ANALISIS EKONOMI DAN PENANGANAN PASCAPANEN PADA JALUR DISTRIBUSI SELADA (Lactuca sativaL) DARI DESA CANDIKUNING, KECAMATAN BATURITI SAMPAI KOTA DENPASAR - Rima Yanti, Ni Putu; Lani Triani, I. G. A.; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 4 (2016): Desember)
This study aims to determine the line distribution  lettuce, post-harvest handling during distribution, calculating the percentage loss of postharvest lettuce, knowing the difference of marketing margin and profit margins in line distribution. The study was conducted between February and April 2016 using a sampling technique  purposive, randomand  snowball sampling. There are 5 line distribution of the Candikuning Village, Baturiti to Denpasar which line I farmer - retailer traditional markets - consumer, line II offarmers - the mediator - the market traders - the consumer, line III farmers - wholesalers - retailers - supermarkets retailers - consumers, line IV farmers - the market traders - a traditional marketretailers - consumers, line V farmers - the mediator - the consumer. Post-harvest handling at the farm level consists of harvesting, sorting, packing, weighing, transporting. Post-harvest handling at the level of collectors consist of transporting, grading, weighing, storage. Postharvest handling on the market traders consists of the transportation, weighing, display. Post-harvest handling at the retail level consists of washing, packaging, weighing, storage, display. Lost post-harvest at the farm level of 12.14%, the level of collectors 2.15%, market traders level of 1.53%, and at the retail level of 3.03%. Marketing and highest profit margin was to Rp 6.000/kg and Rp 3.784/kg which was in the distribution line III, marketing and profit margins as low as Rp 1.666/kg and Rp 1.171/kg was in the distribution line V. Farm gate priceis highest on the line V was 92% of  farm gate price  the lowest for the line III was 77%. Keyword: line distribution, lettuce, postharvest, economic analysis.
Keywords: 117,